From Tinkering to Meddling: Notes on engaging first year art theory students - Messham-Muir, Kit (Journal of University Teaching and Learning Practice, 2012)
This paper considers the two-year-long process of redesigning Art Theory: Modernism, the initial core art theory course at The University of Newcastle in Australia, with the aim of increasing the academic engagement of first year fine art students. First year students are particularly vulnerable to dropping out if they feel disengaged from the University. This paper does not present any grand solutions for teaching today’s first year students. It does, however, consider ways of designing authentic assessment items that acknowledge the new conditions of pedagogy today. This paper offers ideas for engaging first year students, by creating multidimensional resources that include online material that supports yet provokes students; by challenging them with assessments that demand students produce knowledge and not simply retrieve information and; by reconsidering how faculty present information in lectures. The redesigning of the Art Theory: Modernism course was informed by current and ongoing research in teaching and learning and guided by student feedback administered by the Planning, Quality and Reporting unit at the University of Newcastle.